Child-Friendly Mosque: A Study of the Strategic Role of the Baiturrahman Mosque in Empowering the Ummah in the City of Banda Aceh - Marpuah, Marpuah; Atieqoh, Siti; Siagian, Salamah (UIN Sunan Ampel Surabaya, 2024)
As the center of community development, the existence of mosques is now faced with various changes and challenges that continue to roll in the community. The issue of globalization and information is a phenomenon that cannot be ignored. The increasingly dominant information sector in people's lives will certainly have many implications, including opportunities and challenges for Muslims in socializing and actualizing in the wider community. The central role of the mosque is increasingly required to be able to accommodate and keep up with all developments that occur in society. To realize the role of the mosque as the center of activity. This research focuses on the strategic role of the Baiturrahman Mosque in empowering the ummah in the city of Banda Aceh, with a special emphasis on the concept of